Case Report: Reversible chorea arising from severe vitamin B12 deficiency due to autoimmune gastritis: a comprehensive case study - Yang, Meifang; Geng, Yifan; Chen, Zhiren; Zhou, Zixuan; Huang, Wenjuan; Chen, Weiwei; Zhang, Xia (Frontiers in Nutrition, 2025)
Cognitive impairment, ocular neuropathy, sensorimotor polyneuropathy, and subacute combined spinal cord degeneration can all result from a common illness called vitamin B12 insufficiency. With regard to extrapyramidal movement disorders, it is rare, frequently misdiagnosed, and under recognized, which postpones timely treatment. A case study of a 66-year-old man with acute-onset and reversible choreoathetoid symptoms is presented in this publication. A significant vitamin B12 deficiency and an abnormal hypermetabolism in the basal ganglia region were detected by 18F-FDG PET/CT. Remarkably, the patient’s dyskinesia disappeared as soon as vitamin B12 replacement therapy was administered. The patient’s etiology was identified as a mix of vitamin B12 malabsorption and inadequate intake from autoimmune-related gastritis. In order to achieve the best potential therapeutic results, this case highlights the importance of timely and correct diagnosis, timely treatment of vitamin B12 deficiency based on its underlying etiology, and careful research of multiple etiologies.